Analysis of Marketing on Car Consumers: Understanding Consumer Behavior for Effective Marketing Strategies (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Marketers can exist only when they are able to understand consumer's needs and satisfy them. The modern marketing concept for successful management of a firm requires marketers to consider the consumer as the focal point of their business activity. Although it is important for the firms to understand the buyer and accordingly, evolve its marketing strategy, the buyer or consumer continues to be an enigma — sometimes responding the way the marketer wants and, on other occasions, just refusing to buy the product from the same marketer. For this reason, the buyer's mind has been termed as a black box, which should be opened by the seller to be a successful marketer. Understanding how consumers make purchase decisions can help marketing managers in several ways. For example, if a manager knows, through research, that fuel mileage is the most important attribute for a certain target market, the manufacturer can redesign the product to meet that criterion. If the firm cannot change the design in a short run, it can use promotional effort to change consumers' decision making criteria. For example, an automobile manufacturer can advertise a car's maintenance — free features while downplaying fuel mileage.